2001
DOI: 10.1248/cpb.49.246
|View full text |Cite
|
Sign up to set email alerts
|

Triterpene Glycosides from the Cultures of Phytolacca americana.

Abstract: Phytolacca americana L. (Phytolaccaceae) is a perennial plant originating from North America. Its rhizome has been used as a traditional crude diuretic drug in spite of having strong toxicity. A number of triterpenes, their glycosides, and neolignanes have been isolated from the roots of P. americana and identified.1-7) As a part of our search for neurotrophic substances in natural products, we reported the isolation and structure of americanol A (8) and isoamericanol A (9) from the seeds of P. americana.8,9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…4 displayed an aglycone-specific product ion at m/z 533. Elimination of three water molecules, formic acid, and formaldehyde point to an aglycone similar to PA but bearing an additional hydroxyl group, e.g., at the C-2 [37] or the C-16 [38]. Sugar loss of Compound 9 results in a signal detected at m/z 515.…”
Section: Assignment and Fragmentation Of Novel Saponinsmentioning
confidence: 99%
“…4 displayed an aglycone-specific product ion at m/z 533. Elimination of three water molecules, formic acid, and formaldehyde point to an aglycone similar to PA but bearing an additional hydroxyl group, e.g., at the C-2 [37] or the C-16 [38]. Sugar loss of Compound 9 results in a signal detected at m/z 515.…”
Section: Assignment and Fragmentation Of Novel Saponinsmentioning
confidence: 99%
“…The tandem mass data showed that they have the same aglycone. However, this aglycone is 2 mass units higher than that reported from earlier studies (Takahashi et al ., ). Further studies are needed to purify both PRE and PREW using column chromatography and identify their structures and concentrations using 1D and 2D NMR analysis.…”
Section: Resultsmentioning
confidence: 97%
“…They were identified as esculentoside B (1), esculentoside A (2), esculentoside C (3), and esculentoside F (4), respectively, by comparison of their spectral (UV, IR, NMR, and MS, Supplementary Material Tables 1-5) and/or mp data with those of corresponding authentic samples or data from the literature (Liu, 2006;Takahashi et al, 2001;Wang & Yi, 1984).…”
Section: Identification Of Compounds 1-4mentioning
confidence: 99%